Some Views on the EU’s Conditionality and Pre-Accession Policies for the Central and Eastern European Countries - Oana Mocanu (Romanian Journal of European Affairs, 2004)
The end of the Cold War has brought to the European public attention the issue of the ‘forgotten countries’ of the Eastern part of Europe. After years of totalitarian regime, these countries discovered the chance to ‘return to Europe’, to proclaim their freedom and their commitment to the democratic values. At the same time, they were about to face the difficulties of the transition process. Immediately after 1990, the Central and Eastern European countries (CEEC) began their quest for membership of EU. By choosing to open its doors to the Central and Eastern European countries, the European Union did not mean to make the accession process an easy one. On the contrary, EU imposed far stricter conditions for accession, bringing the ‘conditionality’ concept to the debates around the theories of European integration. This article will review some comments on the EU’s conditionality concept and on its effectiveness in support of the CEEC efforts of political and economic transformation.